A decade of Indonesian EFL students - Aimah, Firda Rohmatul; Suhartoyo, Eko (Journal on English as a Foreign Language, 2024)
The discussion regarding the utilization of peer feedback necessitates careful consideration, particularly within the university context. However, the impact of using peer feedback remains indeterminate. This study investigated Indonesian EFL students' perceptions of implementing peer feedback during synchronous and asynchronous periods. A systematic literature review (SLR) method was applied in this study. The data were gathered using the Lens database, evaluated using PRISMA, and coded based on the research questions. The data were separated into two parts over ten years: synchronous (2012-2018) and asynchronous (2019-2022). The findings indicated positive and negative comments. In terms of positive comments, students claimed they got a better understanding; however, in terms of negative comments, students mentioned that the feedback was questionable. The students implemented peer feedback via online and offline media. For online media, students use social media, such as Instagram, Facebook, and websites. In terms of offline media, students used papers. The students also implemented some types of peer feedback, such as support comments, knowledge sharing, negotiation, appreciation, and criticism. The current research limitations and suggestions underscore the need for broader investigations across diverse educational levels and geographical contexts, emphasizing the imperative to enhance the study's generalizability and validity.